Atomic Heterointerface Engineering of Ni2P‐NiSe2 Nanosheets Coupled ZnP‐Based Arrays for High‐Efficiency Solar‐Assisted Water Splitting. (17th May 2022) - Chang, Kai; Tran, Duy Thanh; Wang, Jingqiang; Prabhakaran, Sampath; Kim, Do Hwan; Kim, Nam Hoon; Lee, Joong Hee
Abstract: In this study, heterogeneous nickel phosphide‐nickel selenide (Ni2 P‐NiSe2 ) nanosheets are constructed to coat zinc phosphide‐based nanorods (ZnP NRs) under a unique core@shell architecture, which acts as a highly active multifunctional catalyst toward hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). The catalyst exhibits an overpotential of 79 mV at 10 mA cm –2 for HER and 326 mV at 100 mA cm –2 for OER in freshwater under an alkaline condition. The formation of an open 3D channel architecture derived from highly conductive ZnP@Ni2 P‐NiSe2 nanorods attached nickel foam generates more exposed active sites and promotes fast mass transport. In addition, density functional theory study reveals a synergistic effect between Ni2 P and NiSe2 phase to reduce adsorption free energy and increase the electronic conductivity, thereby accelerating the catalytic reaction kinetics. An electrolyzer of the ZnP@Ni2 P‐NiSe2(+, ‐) requires only cell voltages of 1.54 V (1.43 V) and 1.51 V (1.44 V) to deliver 10 mA cm –2 in freshwater and mimic seawater at 25 °C (75 °C), respectively, along with prospective long‐term stability. Furthermore, the solar energy‐assisted water splitting process demonstrates a solar‐to‐hydrogen efficiency of 19.75%, implying that the catalyst is an effective and low‐cost candidate for water splitting. Abstract : Ni2 P‐NiSe2 nanosheets coating ZnP nanorod arrays under a unique core@shell architecture promote overall water splitting with a required cell voltage of 1.54 V (1.43 V) and 1.51 V (1.44 V) to deliver 10 mA cm –2 in freshwater and mimic seawater at 25 °C (75 °C), respectively. The solar energy‐assisted water splitting process demonstrates a solar‐to‐hydrogen efficiency of 19.75%.